Musical interpretation: case study in musical instrument practice learning vocational high school - Ayu Niza Machfauzia; Suminto A. Sayuti; Djohan Djohan (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This study was intended to reveal: (1) the dimensions of musical interpretation taught; (2) the strategy used by teachers to introduce musical interpretation in instrument practice class; and (3) teacher's ability or competence to teach musical interpretation. This research is case study, with the subjects were 12 teachers responsible for instrument practice class. They were selected using purposive sampling method. The data collection method used were in-depth interviews, passive participation observation, documentation and focus group discussion (FGD). The instrument of study was the researcher herself. Data validity was conduct triangulation by reviewing data acquired from a source. All data then were analyzed using interactive model which included data reduction, data presentation, and conclusion/verification. The results show that: (1) the dimensions of musical interpretation taught in every instrument practice class, were only dimensions of knowledge; (2) the strategy used by teachers when teaching musical interpretation was a direct strategy, teacher-centered learning approach, and used individual approach; and (3) teachers' competence in teaching musical interpretation must be improved, both pedagogical and professional competences.